2016
DOI: 10.1097/opx.0000000000000886
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination of Contact Lens Storage Cases During Daily Wear Use

Abstract: Levels of contamination ranged from 0 to 6.4 Log CFU/storage case well, which varied significantly (p < 0.001) between different CL care solutions, and storage case contamination was not modulated by CL materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…CV staining reveals ability of biofilm to form in the lens case, but not the effect of the solution on its viability. Its use in many studies may underestimate the efficacy of solutions in killing sessile bacteria . Thus, it is essential to perform a viability assay, such as MTT, to determine bactericidal activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CV staining reveals ability of biofilm to form in the lens case, but not the effect of the solution on its viability. Its use in many studies may underestimate the efficacy of solutions in killing sessile bacteria . Thus, it is essential to perform a viability assay, such as MTT, to determine bactericidal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Methods have been developed to assess presence of biofilm. The most commonly utilised technique is staining of biofilm with crystal violet (CV), followed by elution and determination of optical density (OD) . This has been used to examine presence of biofilm in contact lens cases, but there is no standardised method, so comparison between studies may be difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contamination of contact lens cases is reported to be a major cause of infection in contact lens wearers . It has been found that over 90% of the subjects with contaminated case also had contaminated lens or solutions, suggesting that bacteria might be transferred from the case to the lens.…”
Section: Contamination In Contact Lensesmentioning
confidence: 99%
“…The risk of infection is often due to poor personal hygiene in the handling of the lenses and the storage cases, which provide the ideal environment for the growth of bacteria (Dantam et al, 2016;Szczotka-Flynn, Pearlman, & Ghannoum, 2010). Many lens cleaning solutions also risk being contaminated with the bacteria from the contact lens (Lin, Kim, Chen, Kowalski, & Nizet, 2016;Posch, Zhu, & Robertson, 2014;Szczotka-Flynn et al, 2010).…”
Section: Introductionmentioning
confidence: 99%